Peran Nilai, Sikap, dan Kepuasan Kerja dalam Konteks Organisasi - Yasin, Fauzi Sholeh; Muhaimin, Ahmad; Suharyat, Yayat (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to determine the role of Values, Attitudes and Job Satisfaction in organizations. This research is a literature study with a descriptive analysis approach. Meanwhile, the data source used is all literature regarding the role of values, attitudes and job satisfaction in the organizational context. The data is then collected and processed into research results. Data validity is carried out by source triangulation, namely comparing data obtained from various sources. This research shows that the role of values, attitudes and job satisfaction is proven to have a significant dominant influence. The results of this research indicate an increase in satisfaction among organizational members, which can be achieved by encouraging strong work motivation and strengthening commitment to the organization based on organizational cultural values. This effort can be started by creating a conducive work environment; The organization is able to provide all facilities that support the smooth running of learning and teaching. To improve the quality of human resources, apart from effective management, high discipline is required from all members of the organization.